Integrating Mobile Technology into Accounting Practice Instruction: A Strategy for Application and Exploration of Educational Value - Jiang, Liyan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Amid the rapid advancement of mobile technology and the ongoing digital transformation of education, accounting practice instruction has encountered persistent challenges, including the disconnection between theoretical frameworks and practical application and delays in updating instructional resources. Although prior research has demonstrated the potential of mobile technology in this field, limitations remain in aligning technological tools with the construction of knowledge systems. Moreover, fragmented learning experiences often lack systematic integration, and existing knowledge delivery mechanisms exhibit insufficient contextual relevance. To address these issues, this study focuses on the integration of mobile technology within accounting practice instruction. A knowledge graph for accounting practice instruction grounded in mobile technology was proposed, alongside a strategy for the targeted delivery of fragmented knowledge. By restructuring the accounting practice knowledge system and leveraging the visualization and intelligent capabilities of mobile technology, the study seeks to achieve systematic knowledge construction and personalized knowledge delivery. These efforts are intended to enhance the practicality, relevance, and adaptability of accounting practice instruction, thereby underscoring the educational value of mobile technology in the domain of accounting education.